1992
DOI: 10.1073/pnas.89.20.9519
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of autoimmune insulitis in nonobese diabetic mice by expression of major histocompatibility complex class I Ld molecules.

Abstract: Nonobese diabetic (NOD) mice spontaneously develop a T-cefl-mediated autoimmune disease that is similar in many respects to insulin-dependent diabetes mellitus in hu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…Our data suggest that allelic polymorphisms of class I K and/or D genes may be one of the mechanisms in the reduction of the incidence of IDDM in NOD.CTS-H-2 congenic mice. Consistent with this, suppression of insulitis was reported in transgenic NOD mice expressing Ld gene ( 15). Transgenic expression of NOD alleles of class I molecules (Kd and/or Db) in NOD.CTS-H-2 congenic mice would clarify the contribution of class I gene polymorphisms to IDDM susceptibility.…”
Section: Discussionsupporting
confidence: 70%
“…Our data suggest that allelic polymorphisms of class I K and/or D genes may be one of the mechanisms in the reduction of the incidence of IDDM in NOD.CTS-H-2 congenic mice. Consistent with this, suppression of insulitis was reported in transgenic NOD mice expressing Ld gene ( 15). Transgenic expression of NOD alleles of class I molecules (Kd and/or Db) in NOD.CTS-H-2 congenic mice would clarify the contribution of class I gene polymorphisms to IDDM susceptibility.…”
Section: Discussionsupporting
confidence: 70%
“…However, we could not discriminate the role of K k and D k expressed in T cells of AKR origin in the reconstituted NOD.scid-RIP-B7.1 mice. The mechanisms of T1D prevention by MHC class I genes of k haplotype expressed in T cells remain unclear, although a previous study suggested regulatory mechanisms induced by the expression of a T1D-resistant class I gene (40). Indeed, the development of regulatory NKT cells requires expression of MHC-I-like CD1d/␤ 2 m complex on the surface of double-positive thymocytes (41) that were mostly donor origin in the reconstituted mice.…”
Section: Discussionmentioning
confidence: 99%
“…All animal procedures were done in accordance with the guidelines of the Animal Care and Use Committee of the Jackson Laboratory and the University of Massachusetts Medical School and conformed to the recommendations in the Guide for the Care and Use of Laboratory Animals (National Institutes of Health, Bethesda, MD, USA). Supplemental Figure S1 and Supplemental Table S1 provide a direct comparison of the relevant strains used for experiments (28,29,(33)(34)(35)(36).…”
Section: Micementioning
confidence: 99%